ANALISIS WACANA PADA PIDATO ABRAHAM LINCOLN â€œAddress at Gettysburg, Pennsylvania. November 19, 1863â€ - Rambing Tu, Adrianus Riky (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT The title of this minor thesis is Discourse Analysis in Abraham Lincoln Speech â€œAddress at Gettysburg, Pennsylvania, November 19, 1863â€. It is an attempt to analyze and explain the discourse analysis items that hidden in Abraham Lincoln speech to be applied in recent live of society. The method used in this research is taken from Alba-Juez (2008:20) and supported the theory by De Beaugrande & Dressler (1986:8) and Aarts and Aarts (1982: 4). The theory consists of seven items, they are: Cohesion: pronoun, substitution, ellipsis, conjunction, lexical, Coherence: mark coherence, and unmark coherence, Intentionality, Acceptability, Informatifity, Situationality, and Intertextuality. The speech and the history were taken from internet as an object of research. The result showed that this speech occupied the seven items suggested by Alba-juez. Â  Â  Keywords:Â  discourse analysis, speech, war, Abraham Lincoln.